2D Black Phosphorus: from Preparation to Applications for Electrochemical Energy Storage. Issue 5 (23rd February 2018) - Wu, Shuxing; Hui, Kwan San; Hui, Kwun Nam
Abstract: Black phosphorus (BP) is rediscovered as a 2D layered material. Since its first isolation in 2014, 2D BP has triggered tremendous interest in the fields of condensed matter physics, chemistry, and materials science. Given its unique puckered monolayer geometry, 2D BP displays many unprecedented properties and is being explored for use in numerous applications. The flexibility, large surface area, and good electric conductivity of 2D BP make it a promising electrode material for electrochemical energy storage devices (EESDs). Here, the experimental and theoretical progress of 2D BP is presented on the basis of its preparation methods. The structural and physiochemical properties, air instability, passivation, and EESD applications of 2D BP are discussed systemically. Specifically, the latest research findings on utilizing 2D BP in EESDs, such as lithium‐ion batteries, supercapacitors, and emerging technologies (lithium–sulfur batteries, magnesium‐ion batteries, and sodium‐ion batteries), are summarized. On the basis of the current progress, a few personal perspectives on the existing challenges and future research directions in this developing field are provided. Abstract : Black phosphorus (BP) is rediscovered as a 2D layered material. The experimental and theoretical progress of 2D BP on the basis of its preparation methods is presented. The structural and physiochemical properties, air instability, passivation, and electrochemical energy storage applications of 2D BP are discussed systemically.